SUSTAINABLE ENERGY HOMES (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Independent energy house become an important for modern housing now a day. Solar energy is one of the renewable and sustainable energy. Optimization Solar energy can be done by considering how long the sun light can directly on solar cells. Optimizing solar cells performance needs to be done, to increase the amount of stored electricity. In addition to the direction of sunlight, the weather also directly affects the performance of solar cells. The result of the direction, it has an effect on the building shape, façade and the room order, so the building will have a shape that according to function. Form follows function is effectively for adjusting room space. This Residential building will be appropriate with urban context, especially in city of Malang. Form follows function, the way to find sustainable house and independent energy house for residential house design. The design plan of Independent energy home with form follows function approach will be done in Malang city.